"God loves me no matter how I am": a phenomenological analysis of the religious and spiritual experiences of HIV-infected African-American women with depression. Issue 2 (7th February 2016) - Himelhoch, Seth; Njie-Carr, Veronica
ABSTRACT: Depression is associated with increased HIV morbidity and mortality, particularly among African-American women (AAW) in the United States. The purpose of this qualitative study was to explore religious practices, spiritual beliefs, and experiences among AAW with co-occurring HIV infection and depression. A transcendental phenomenological study design was used to explore the experiences of AAW's religion and spirituality after an HIV diagnosis and living with depression. The four themes that were identified included: Religious Conflict and Return to Religious Practices; Religious Fortitude Broken and Feeling Judged; Spiritual Connection is More Powerful than Attending Church Services; and Spiritual Healing and Re-Connecting with Spirituality. These findings suggest that the distinction between internal and external manifestations of spirituality is important and that given the current religious climate, interventions that focus on supporting internal spiritual practice may be a more important and effective approach for AAW with co-occurring HIV infection and depression.